Soy Isoflavones Accelerate Glial Cell Migration via GPER-Mediated Signal Transduction Pathway - Ariyani, Winda; Miyazaki, Wataru; Amano, Izuki; Hanamura, Kenji; Shirao, Tomoaki; Koibuchi, Noriyuki (Frontiers in Endocrinology, 2020)
Soybean isoflavones, such as genistein, daidzein, and its metabolite, S-equol, are widely known as phytoestrogens. Their biological actions are thought to be exerted via the estrogen signal transduction pathway. Estrogens, such as 17β-estradiol (E2), play a crucial role in the development and functional maintenance of the central nervous system. E2 bind to the nuclear estrogen receptor (ER) and regulates morphogenesis, migration, functional maturation, and intracellular metabolism of neurons and glial cells. In addition to binding to nuclear ER, E2 also binds to the G-protein-coupled estrogen receptor (GPER) and activates the nongenomic estrogen signaling pathway. Soybean isoflavones also bind to the ER and GPER. However, the effect of soybean isoflavone on brain development, particularly glial cell function, remains unclear. We examined the effects of soybean isoflavones using an astrocyte-enriched culture and astrocyte-derived C6 clonal cells. Isoflavones increased glial cell migration. This augmentation was suppressed by co-exposure with G15, a selective GPER antagonist, or knockdown of GPER expression using RNA interference. Isoflavones also activated actin cytoskeleton arrangement via increased actin polymerization and cortical actin, resulting in an increased number and length of filopodia. Isoflavones exposure increased the phosphorylation levels of FAK (Tyr397 and Tyr576/577), ERK1/2 (Thr202/Tyr204), Akt (Ser473), and Rac1/cdc42 (Ser71), and the expression levels of cortactin, paxillin and ERα. These effects were suppressed by knockdown of the GPER. Co-exposure of isoflavones to the selective RhoA inhibitor, rhosin, selective Cdc42 inhibitor, casin, or Rac1/Cdc42 inhibitor, ML-141, decreased the effects of isoflavones on cell migration. These findings indicate that soybean isoflavones exert their action via the GPER to activate the PI3K/FAK/Akt/RhoA/Rac1/Cdc42 signaling pathway, resulting in increased glial cell migration. Furthermore, in silico molecular docking studies to examine the binding mode of isoflavones to the GPER revealed the possibility that isoflavones bind directly to the GPER at the same position as E2, further confirming that the effects of the isoflavones are at least in part exerted via the GPER signal transduction pathway. The findings of the present study indicate that isoflavones may be an effective supplement to promote astrocyte migration in developing and/or injured adult brains.